Mesure de l’acuité visuelle par la technique du regard préférentiel : Revue des méthodes - Laurin, L.; Gresset, J.; Beaulne, C. (Canadian Journal of Optometry, 2026)
Preferential looking methods efficientfy measure the visual acuity of infants and developmentally delayed subjects. The procedures use grids as stimuli and do not require any verbal response from the subjects. Early preferential looking methods for the assessment of visual acuity relied upon formal, statistically rigorous, psychophysical procedures that were lengthy and could be easily applied only in laboratory studies. From a clinical point of view, Tellet acuity cards are very interesting. They are easy to handle and they give good results in less than five minutes. However, they are not as statistically rigorous as traditional preferential looking techniques.